Duckweed Species Genotyping and Interspecific Hybrid Discovery by Tubulin-Based Polymorphism Fingerprinting - Braglia, Luca; Lauria, Massimiliano; Appenroth, Klaus J.; Bog, Manuela; Breviario, Diego; Grasso, Aldo; Gavazzi, Floriana; Morello, Laura (Frontiers in Plant Science, 2021)
Duckweeds (Lemnaceae) are the smallest and fastest growing angiosperms. This feature, together with high starch production and good nutritional properties, make them suitable for several applications, including wastewater treatment, bioenergy production or feed and food supplement. Due to their reduced morphology and great similarity between diverse species, taxonomic identification of duckweeds is a challenging issue even for experts. Among molecular genotyping methods, DNA barcoding is the most useful tool for species identification without need for cluster analysis. The combination of two plastid barcoding loci is now considered the gold standard for duckweeds classification. However, not all species can be defined with confidence by these markers and a fast identification method able to solve doubtful cases is missing. Here we show the potential of Tubulin-based Polymorphism (TBP), a molecular marker based on intron length polymorphisms of β-tubulin loci, in the genomic profiling of the genera Spirodela, Landoltia and Lemna. Ninety-four clones were analyzed, including at least two representatives of each species of the three genera, with a special focus on the very heterogeneous species Lemna minor. We showed that a single PCR amplification with universal primers, followed by agarose gel analysis, was able to provide distinctive fingerprinting profiles for 10 out of 15 species. Cluster analysis of Capillary Electrophoresis-TBP data provided good separation for the remaining species, although the relationship between L. minor and L. japonica was not fully resolved. However, accurate comparison of TBP profiles provided evidence for the unexpected existence of intraspecific hybrids between L. turionifera and L. minor, as further confirmed by AFLP and sequence analysis of a specific β-tubulin locus. Such hybrids could possibly correspond to L. japonica, as originally suggested by E. Landolt. The discovery of interspecific hybrids opens a new perspective to understand the speciation mechanisms in the family of duckweeds.